A current perspective on antimicrobial resistance in Southeast Asia - Zellweger, Raphaël M; Carrique-Mas, Juan; Limmathurotsakul, Direk; Day, Nicholas P. J; Thwaites, Guy E; Baker, Stephen; Ashley, Elizabeth; de Balogh, Katinka; Baird, Kevin; Basnyat, Buddha; Benigno, Carolyne; Bodhidatta, Ladaporn; et al. (Journal of antimicrobial chemotherapy, 2017)
Southeast Asia, a vibrant region that has recently undergone unprecedented economic development, is regarded as a global hotspot for the emergence and spread of antimicrobial resistance (AMR). Understanding AMR in Southeast Asia is crucial for assessing how to control AMR on an international scale. Here we (i) describe the current AMR situation in Southeast Asia, (ii) explore the mechanisms that make Southeast Asia a focal region for the emergence of AMR, and (iii) propose ways in which Southeast Asia could contribute to a global solution.